2009
DOI: 10.1017/s1355617709990324
|View full text |Cite
|
Sign up to set email alerts
|

Younger age is a good predictor of better executive function after surgery for pituitary adenoma in adults

Abstract: Pituitary adenomas, even after successful treatment, are associated with cognitive dysfunctions. We hypothesized that an association between the age of the patients at pituitary surgery and neuropsychological outcome may exist. Forty-two patients (mean age 51 +/- 10 years) who had been successfully treated for pituitary adenoma (surgery with or without subsequent radiotherapy) underwent neuropsychological testing. Age at treatment (mean 37 +/- 11 years) was significantly associated with Trail Making Test, Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…This could be because of a more neuroplastic brain at younger age and special (vascular) vulnerability in the elderly patients. 30 In our study, the RT+ group was younger than the RT) group at pituitary surgery and as a result had a longer average time since surgery. However, both age at surgery and time since surgery or radiotherapy were not associated with cognitive functioning (data not shown).…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…This could be because of a more neuroplastic brain at younger age and special (vascular) vulnerability in the elderly patients. 30 In our study, the RT+ group was younger than the RT) group at pituitary surgery and as a result had a longer average time since surgery. However, both age at surgery and time since surgery or radiotherapy were not associated with cognitive functioning (data not shown).…”
Section: Discussionmentioning
confidence: 52%
“…Younger age at surgery could be a favourable recovery factor after brain surgery. This could be because of a more neuroplastic brain at younger age and special (vascular) vulnerability in the elderly patients 30 . In our study, the RT+ group was younger than the RT− group at pituitary surgery and as a result had a longer average time since surgery.…”
Section: Discussionmentioning
confidence: 57%
“…4,6,7 Furthermore, younger age at surgery in patients with functioning or non-functioning adenomas is beneficial to a better neurocognitive outcome, but existing studies have investigated patients only once at a randomly chosen time. 8,9 To investigate whether cognitive function improves after surgical treatment, we performed a prospective longitudinal study comprising 106 patients with pituitary tumors. We also investigated whether there was an approximate temporal gradient for the observed improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, our data point to an impairment of cerebral networks necessary for certain aspects of executive function after surgery for pituitary adenomas. It is worth noting that these brain lesions may underlie recovery, given that we have recently shown that younger age is a good predictor of better executive function after surgery for pituitary adenoma in adults (Müssig et al, 2009).…”
Section: Discussionmentioning
confidence: 99%